Characteristics of turbulent flames in a confined and pressurised jet-in-hot-coflow combustor. (December 2022) - Proud, D.B.; Evans, M.J.; Chan, Q.N.; Medwell, P.R.
Abstract: Combustion in hot and low oxygen environments—such as those encountered in practical devices including inter-turbine burners and sequential gas turbines—is not yet fully understood at a fundamental level, particularly in terms of the effects of pressure. To meet this gap in understanding, a confined-and-pressurised jet-in-hot-coflow (CP-JHC) combustor has been developed to facilitate optical diagnostics of turbulent flames in hot and vitiated coflows for the studies of flame stabilisation, structure and soot formation at elevated pressures. The CP-JHC burner has been designed for steady operation at 10 bar with internal temperatures of up to 1975 K, with a water-cooled central jet issuing into a hot oxidant stream of combustion products from a non-premixed natural gas/H2 burner. This work describes the key features and operational capabilities of the CP-JHC burner and presents a selection of experimental results showing characteristics not previously available. Specifically, temperature measurements of the hot coflow are used to estimate the enthalpy deficit of the stream, revealing an increase in thermal efficiency with increasing heat input, and a decrease with increasing pressure. Chemiluminescence imaging of OH ∗ and CH ∗ is performed for turbulent jet flames to study the flame structure under various operating conditions, and true-colour imaging results are also included to highlight the change in soot formation under elevated pressures. The mean images indicate a change in stabilisation behaviour with changes in pressure and jet Reynolds number ( Re jet ), which is further investigated by a statistical analysis of the short-exposure CH ∗ images. This analysis reveals that an increase in Re jet from 10, 000 to 15, 000 leads to an increase in the mean lift-off height (from the jet exit plane) from approximately 1.5 to 6 jet diameters at atmospheric pressure, while the flames at elevated pressures show significantly less variation and tend to stabilise at the jet exit for P  > 3.5 bar(a). The experimental findings are complemented by numerical simulations of laminar opposed flow flames, providing additional insights into the fundamental chemical kinetics effects which influence these flames. In particular, a monotonic reduction in both the maximum and integrated OH ∗ and CH ∗ mass fractions is observed with increasing pressure. This reduction is particularly pronounced at lower pressures, with a reduction to 10% of the atmospheric-pressure value at 3 bar(a) for the integrated OH ∗ mass fraction. Additionally, this behaviour is shown to be related to the combined effects of a shift in the formation pathways and the increased impact of collisional quenching. Highlights: A novel apparatus for elevated-pressure combustion is introduced and characterised. Turbulent jet flames studied via chemiluminescence imaging (OH ∗ and CH ∗ ). Changes in OH ∗ and CH ∗ intensity and flame stabilisation observed with pressure. Soot is seen to form in the near-field for 1:1H2 :NG flames for P ≥ 5.0 bar. Effect of pressure on OH ∗ and CH ∗ reactions explored via laminar flame simulations.